REGIONAL TRAE BLOCS : A CASE STUDY OF THE WELFARE IMPACT OF THE EUROPEAN UNION ON INDIA AND KENYA - Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
Some countries, including the big player in the world economy, the USA , believe that free trade liberalization based on principles of non discriminatory and multilateral bases as well as an open market will improve the welfare of many countries. However, other countries do not follow the idea of trade liberalization and hence respond by forming regional trading blocs. Therefore, the existence of such trading blocs will be examined, whether they are a 'building blocks' or a 'stumbling blocks, for sustaining the free trade liberalization. And hence, this paper focuses on three main parts: rationalization of the establishment of trading blocs; identification of the critical factors for the success of these blocs; and presentation of empirical evidence for the welfare implications of the trade diverting effects of the European Union through the analysis of two less developed countries, India and Kenya.